1983
DOI: 10.1002/ajmg.1320150408
|View full text |Cite
|
Sign up to set email alerts
|

Part II. Amyoplasia: Twinning in amyoplasia—a specific type of arthrogryposis with an apparent excess of discordantly affected identical twins

Abstract: We report on 11 cases of amyoplasia in one of identical twins. In total, 135 patients with amyoplasia were ascertained from a study of 350 patients with multiple congenital joint contractures (arthrogryposis). These 11 cases of identical twins with amyoplasia represent 8% of our patients with amyoplasia. At least 18 sets of twins with congenital contractures have been reported previously. However, only four of these appear to involve identical twins discordant for amyoplasia. Thus, 15 cases in which only one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 9 publications
1
38
0
1
Order By: Relevance
“…An excessive incidence of amyoplasia was reported in monozygotic twins [2,7] , and in almost all the reported cases, only one of each pair of twins was affected [2,[7][8][9][10][11][12] . In cases where arthrogryposis affected one of the twin pairs, the affected child usually had a lower birth weight than its normal twin [2,8,13] . Anterior horn cell atrophy was demonstrable on postmortem examination of the affected twin [9] as in our case, or suggested on electromyography [14] , and could be focal or generalized [3] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An excessive incidence of amyoplasia was reported in monozygotic twins [2,7] , and in almost all the reported cases, only one of each pair of twins was affected [2,[7][8][9][10][11][12] . In cases where arthrogryposis affected one of the twin pairs, the affected child usually had a lower birth weight than its normal twin [2,8,13] . Anterior horn cell atrophy was demonstrable on postmortem examination of the affected twin [9] as in our case, or suggested on electromyography [14] , and could be focal or generalized [3] .…”
Section: Discussionmentioning
confidence: 99%
“…It has an excessive and discordant occurrence in monozygotic twins, representing 8% of patients in the series of Hall et al [2] . A case of arthrogryposis with clinical features suggestive of amyoplasia in a monochorionic twin pregnancy with conjoined umbilical cords will be presented and the possible aetiology will be discussed in relation to the findings.…”
mentioning
confidence: 99%
“…Most patients have normal intelligence. In one series, 10% of the patients had abdominal abnormalities such as gastroschisis or bowel atresia 11 . Clinical series 10 have shown that 84% of the children have symmetric involvement of the upper and lower limbs; other variations of presentation include upper limb only, lower limb only, or asymmetric patterns of involvement 5 .…”
Section: Classification Of Arthrogryposismentioning
confidence: 99%
“…I found that one-third had only limbs involved, one-third had limbs plus other body areas involved, and one-third were lethal or led to severe developmental delay (31). Of the living individuals affected with arthrogryposis, one-third also had amyoplasia-a newly recognized disorder identified from clinical observation (91,93,127). I distinguished different entities on a clinical basis (90,92,94,95), Lynn Staheli devised new orthopedic therapies for specific deformities, and the rehabilitation group discovered the importance of stretching and splinting-all now mainstays of care for individuals with arthrogryposis.…”
Section: The 1970smentioning
confidence: 99%